New species of Cerambycidae from Panama, with new distribution records (Coleoptera: Cerambycidae) - Bezark, Larry G.; Tyson, William H.; Schiff, Nathan M. (Zootaxa, 2013)
Two new species of Cerambycidae, Tessaropa elizabeth Bezark, sp. nov. (subfamily Cerambycinae, tribe Methiini ) and Anelaphus cordiforme Tyson, sp. nov. (subfamily Cerambycinae, tribe Elaphidiini), are described from the western part of the Darien, Panama. Nine new country records for Panama are reported for the following species: Adetus linsleyi Martins & Galileo, Estola strandiella Breuning, Nubosoplatus inbio Swift, Paranisopodus heterotarsus Monné & Martins, Pempteurys sericans Bates, Rosalba costaricensis (Melzer), Tomopterus brevicornis Giesbert, Psapharochrus nigricans (Lameere), and Oedudes bifasciata (Bates).